2020
DOI: 10.5204/ijcjsd.v10i1.1538
|View full text |Cite
|
Sign up to set email alerts
|

Doing Marginalized Motherhood: Identities and Practices among Incarcerated Women in Mexico

Abstract: This study examines the mothering practices and identities of incarcerated women in Mexico. Data gathered from repeated life-story interviews with 12 women, were analyzed to describe mothering practices in the different phases of incarcerated women’s’ lives. We argue that knowledge of the Latin American context is crucial to understand their experiences of motherhood. In a society based on familism and marianismo identities that suffers from a lack of welfare institutions, motherhood provided a way for sociall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Having said this, our experience from research with other groups of people who use drugs in very different contexts (e.g., Copes et al, 2008;Grundetjern & Sandberg, 2012;Sandberg et al, 2020) and the extensive literature on drug use and symbolic boundaries (for a review, see Copes, 2016) indicate that what we have identified here are relatively general ways for women to present and relate to functional drug use. Arguably, women who use heavily stigmatized drugs will despite geographical, cultural, racial, and other differences tend to embed their protective stories, symbolic boundaries, and perception of functional drug use in cultural narratives of motherhood and healthy moral, physical, and emotional health.…”
Section: Discussionmentioning
confidence: 84%
“…Having said this, our experience from research with other groups of people who use drugs in very different contexts (e.g., Copes et al, 2008;Grundetjern & Sandberg, 2012;Sandberg et al, 2020) and the extensive literature on drug use and symbolic boundaries (for a review, see Copes, 2016) indicate that what we have identified here are relatively general ways for women to present and relate to functional drug use. Arguably, women who use heavily stigmatized drugs will despite geographical, cultural, racial, and other differences tend to embed their protective stories, symbolic boundaries, and perception of functional drug use in cultural narratives of motherhood and healthy moral, physical, and emotional health.…”
Section: Discussionmentioning
confidence: 84%
“…Relationship to children was important in all interviews, more abstractly for men (Sandberg et al, forthcoming) and in more practical terms for women (Sandberg et al, 2020). Women also tended to speak more extensively about their children.…”
Section: Discussionmentioning
confidence: 99%
“…As seen above, the prison infrastructure and administrative apparatus tend to orient organizational structures in such a way that they preserve traditional gender roles (sport, maternity, etc). For marginalized Mexican women, raising a child is an interchangeable responsibility between women of the extended family, which continues even during incarceration (Sandberg et al, 2020). Men, on the other hand, seem to be able to disregard their financial responsibility when incarcerated, and instead hang on to their fatherhood through stories of their dreams to be emotionally supportive and caring fathers, especially after their release (Sandberg et al, forthcoming).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even while incarcerated, women’s relationships with their families of origin remain important to their identity (Leverentz, 2011). Motherhood is arguably one of the most stable social identities for women; consequently, coping with separation from family can negatively affect reintegration (Celinska & Siegel, 2010; Sandberg et al, 2020). Reclaiming relationships with children can be difficult for the formerly incarcerated due to financial hardship, social stigma, shame, and struggles with recovery from addiction (Celinska & Siegel, 2010; Cooper-Sadlo et al, 2018; Larsen, 2017; Nyamathi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%